Solve the following system of equations using the elimination method:
2x + 3y = 8
4x - 2y = 10
Step 1: Multiply the first equation by 2 to make the coefficients of x in each equation the same:
4x + 6y = 16
4x - 2y = 10
Step 2: Subtract the second equation from the first equation:
(4x + 6y) - (4x - 2y) = 16 - 10
4x + 6y - 4x + 2y = 6
8y = 6
y = 6/8
y = 3/4
Step 3: Substitute the value of y back into one of the original equations to solve for x. Let's use the first equation:
2x + 3(3/4) = 8
2x + 9/4 = 8
2x = 8 - 9/4
2x = 32/4 - 9/4
2x = 23/4
x = 23/4 * 1/2
x = 23/8
Therefore, the solution to the system of equations is x = 23/8 and y = 3/4.
solving with elimination practice question 4 of 5
1 answer